Membangun Karakter Anti korupsi Dengan Menggali Potensi Generasi Z - Jhordy; Zikri; Leo (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Building an anti-corruption character among the younger generation, especially Generation Z, is very important because corruption is the main challenge that hinders development in Indonesia. Generation Z born between 1995 and 2010 has great potential as agents of change thanks to their access to information and technology. This study investigates useful methods that generation Z can use to build an anti-corruption character through education that incorporates ethical values. Based on previous research, it was found that providing the younger generation with anti-corruption education starting from an early age can increase their anti-corruption awareness and attitudes. In addition, collaboration between family, community and government is very important to create an environment that supports the value of integrity. It is hoped that Generation Z can contribute significantly to building a society free from corrupt practices if they use the right strategies. This article provides insight into the role played by generation Z in fighting corruption and the impact it will have on the future of the country.